Menghindari Tanggung Jawab dengan Mencantumkan Klausula Eksonerasi dalam Perjanjian Baku: Legalkah? - Supastika, I Komang; Dedy Priyanto, I Made (Kertha Negara : Journal Ilmu Hukum, 2024)
The research in this article aims to find out the reasons why exoneration clauses are possible to be included in a standard agreement and to analyze the legality of the inclusion of exoneration clauses in standard agreements according to the Consumer Protection Act. This article applies normative legal research methods as well as statutory approaches and comparative approaches. The way to analyze and review used in this article is a descriptive technique. Based on the results of the study, it can be seen that the principle of freedom of contract as stipulated in Articles 1320 and 1338 of the Civil Code is a fundamental reason for business actors to be able to include exoneration clauses in a standard agreement, because according to this principle the parties have the flexibility to determine the clauses to be agreed upon in an agreement, this is strengthened by the provisions as contained in Article 1493 of the Civil Code. The inclusion of exoneration clauses in a standard agreement by business actors is also possible due to the non-implementation of control by the government as contained in Article 8 of Government Regulation Number 58 of 2001. The exoneration clause is contained in the provisions of Article 18 Paragraph (1) Letter a of the Consumer Protection Act. Based on the provisions of Article 18 and Article 62 Paragraph (1) of the Consumer Protection Act, it is known that the inclusion of an exoneration clause in a standard agreement has no legality, which is in line with the restrictions provided by Article 1494 of the Civil Code.